The effect of opium addiction on postoperative intraabdominal adhesion in rat - J Vahedian-Ardakani; H.R Bahjati (Journal of Kerman University of Medical Sciences, 2001)
intraperitoneal adhesion formation is a major cause of intestinal obstruction and inferlitity.previous abdominal or pelvic surgery are the most common causes of intraperitoneal adhesion formation.addiction to opium and moephine is not only an important social and individual problem in the world but also affects human physiology and immune system.this randomized double-blind study was designed to investigate the effect of addiction to morphine and opium on postopertive intraperitoneal adhesion formation in rats.63 female rat were divided into three groups and maintained under routinelaboratory condition.there was no addiction in control group.morphine addiction was induced by adding moephine sulfate powder in dirnking water(0.4mg/kg for a duration of 28 days)and in opium group by adding opium tablets in drinking water as powder.after confirmation of addiction by subcutaneous injection of naloxan all rats underwent laparotomy and the serosa of the cecum was scratched over a 5mm*5mm area.the second laparotomy was performed on 30th postoperative day.the extent of intraperitoneal adhesions were quantified based on a scoring system modified by swolin and the informations were analysed by chi-square test.the results showed a significant reduction of intraperitoneal adhesin in addicted group compared with nonaddicted group(p<0.05). it is concluded that addiction to morphine and opium decreases postoperative intraperitoneal adhesion formation in rats.